Homoepitaxial growth of a-plane GaN layers by reaction between Ga2O vapor and NH3 gas. (30th April 2015) - Sumi, Tomoaki; Taniyama, Yuuki; Takatsu, Hiroaki; Juta, Masami; Kitamoto, Akira; Imade, Mamoru; Yoshimura, Masashi; Isemura, Masashi; Mori, Yusuke
Abstract: Growth of high-quality a -plane GaN layers was performed by reaction between Ga2 O vapor and NH3 gas at a high temperature. Smooth a -plane GaN epitaxial layers were obtained on a -plane GaN seed substrates sliced from thick c -plane GaN crystals. Growth rate increased with increasing Ga2 O partial pressure. An a -plane GaN layer with a growth rate of 48 µm/h was obtained. The X-ray rocking curve (XRC) measurement showed that the full widths at half maximum (FWHMs) of GaN with the incident beam parallel and perpendicular to the [0001] direction were 29–43 and 29–42 arcsec, respectively. Secondary ion mass spectrometry (SIMS) measurement revealed that oxygen concentration decreased at a high temperature. These results suggest that growth of a -GaN layers using Ga2 O vapor and NH3 gas at a high temperature enables the generation of high-quality crystals.